2018
DOI: 10.1002/brb3.1130
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomic analysis of intracerebral hemorrhage in rats with a focus on brain energy metabolism

Abstract: IntroductionIntracerebral hemorrhage (ICH) is a lethal cerebrovascular disorder with a high mortality and morbidity. The pathophysiological mechanisms underlying ICH‐induced secondary injury remain unclear.MethodsTo examine one of the gaps in the knowledge about ICH pathological mechanisms, isobaric tag for relative and absolute quantification (iTRAQ)‐based liquid chromatography‐tandem mass spectrometry (LC‐MS/MS) was used in collagenase‐induced ICH rats on the 2nd day.ResultsA total of 6,456 proteins were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 82 publications
0
15
0
Order By: Relevance
“…Although there are no previous studies on the proteome of human brain following ICH, a study in a pig model of ICH showed differences in proteomic expression of whole tissue at 24 h and at 60 days compared to controls 38 . Another study in a rat model of acute ICH showed differential protein expression 39 , as did a tissue proteomic study of collagenase-induced ICH in rats at 2 days post-ICH 40 . These animal studies used whole tissue samples, and although interesting they present significant methodological differences to our present study which uses microdialysis for sampling, thus making direct comparisons difficult.…”
Section: Discussionmentioning
confidence: 94%
“…Although there are no previous studies on the proteome of human brain following ICH, a study in a pig model of ICH showed differences in proteomic expression of whole tissue at 24 h and at 60 days compared to controls 38 . Another study in a rat model of acute ICH showed differential protein expression 39 , as did a tissue proteomic study of collagenase-induced ICH in rats at 2 days post-ICH 40 . These animal studies used whole tissue samples, and although interesting they present significant methodological differences to our present study which uses microdialysis for sampling, thus making direct comparisons difficult.…”
Section: Discussionmentioning
confidence: 94%
“…After awakening, the rats were assessed by masked observer through modified Neurological Severity Score (mNSS) ( Table 1). 18 The score (>8.5 points) was the success of the model. The control group rats were treated with 3 µL saline instead of collagenase and heparin sodium.…”
Section: Intracerebral Hemorrhage Modelmentioning
confidence: 99%
“…Not only are primary hemorrhage-associated injuries of relevance, but secondary ICH-related injuries must also be taken into account [ 25 ]. For instance, the dysregulation of energy metabolism occurs in the setting of ICH, which could be a major contributor to secondary injury [ 26 , 27 , 28 ]. Furthermore, oxidative stress, inflammation, and iron toxicity also play important roles [ 2 , 29 ] [ 30 ].…”
Section: Discussionmentioning
confidence: 99%